The punitive state: crime, punishment, and imprisonment across the United States - Frost, Natasha (Criminal justice recent scholarship, 2006)
The punitive turn -- Understanding the punitive turn -- Trends in imprisonment -- Exploring variations in imprisonment -- Explaining variations in imprisonment -- The problem with punitiveness -- Measuring punitiveness -- Punitiveness across measures -- Punitiveness across offense types -- Punitiveness over time, 1990-2000 -- Understanding variations in punitiveness